Workflow-based organ dosimetry in esophageal stent placement: Quantitative assessment of CT and fluoroscopic radiation contributions - Cakar, Ekrem; Karagulle, Onur Olgac; Rakici, Ibrahim Taskin; Bayrak, Savas; Kayaokay, Duygu Tuncman; Kesmezacar, Fahrettin Fatih; Gunay, Osman; Demir, Mustafa; Oksuz, Didem Colpan; AlMisned, Ghada; Tekin, H. O. (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Fluoroscopy-guided esophageal stent placement is a widely used palliative intervention for malignant dysphagia and is typically preceded by thoracic computed tomography (CT) imaging. Although radiation exposure from CT and fluoroscopy has been individually investigated, experimental data quantifying organ-specific absorbed dose within the complete clinical workflow remain limited. This study aimed to experimentally evaluate absorbed doses in selected thoracic organs during sequential CT imaging and fluoroscopy-guided esophageal stent placement using calibrated thermoluminescent dosimeters (TLDs) in an anthropomorphic Alderson Rando phantom. Eighteen anatomical locations were monitored. During CT imaging, absorbed doses ranged from 2.50 +/- 0.29 mGy (esophagus) to 4.83 +/- 0.51 mGy (left middle lung), demonstrating a relatively homogeneous distribution. In contrast, fluoroscopy-guided intervention produced higher and more heterogeneous dose patterns, with peak exposure at the thoracic spinal cord (49.96 +/- 2.84 mGy) and esophagus (24.42 +/- 4.58 mGy). Superficial breast doses during fluoroscopy remained minimal (<0.5 mGy). Cumulative absorbed doses exceeded 53 mGy at the spinal cord and approached 27 mGy at the esophagus when both procedural phases were combined. It can be concluded that fluoroscopy is the dominant contributor to deep thoracic organ dose during esophageal stenting and highlights the importance of workflow-based cumulative dose assessment for optimization of interventional imaging protocols.
Keywords: Organ dose distribution; Esophageal stent; Fluoroscopy-guided intervention; Computed tomography (CT); Thermoluminescent dosimetry (TLD); CANCER; RISK; Chemistry; Nuclear Science & Technology; Physics